Effects of an Enzymatically Hydrolyzed Yeast and Yeast Culture Combined with Flavomycin and Monensin on Finishing Broiler Chickens - Gomez, Sergio; Angeles, Maria de Lourdes (International Journal of Poultry Science, 2011)
An experiment was carried out to evaluate the relationship of an Enzymatically Hydrolyzed Yeast (EHY) and yeast culture combined with flavomycin and monensin (F + M) under two levels of Digestible Lysine (DLYS) on the growth performance, carcass measurements, nutrient retention and AMEn in broilers. One hundred and thirty two 35 d old Ross B308 male broilers individually housed in holding cages were used. Broilers were assigned to a factorial arrangement of 2 levels of EHY (0 and 1 kg/ton of feed) x 2 levels of F + M (0.0 and 0.05,0.50 kg/ton) x 2 DLYS levels (0.85 and 0.95%). The experiment lasted 2 wks. Results were subjected to analysis of varianza. EHY-fed broilers showed a trend for greater (p